Intracranial intrasellar kissing carotid arteries: case report - Pereira Filho,Arthur de Azambuja (2007)
Intracranial "kissing" carotid arteries are a rare variant of the carotid arteries, where both internal carotid arteries deviate medially and touch each other near the midline within the sphenoid sinus or the sphenoid bone, including the sella. This anomaly is particularly important since it may cause or mimic pituitary disease and also may complicate transsphenoidal surgery. We report a rare case of intracranial intrasellar kissing carotid arteries in a 57-years-old woman that was submitted to a computed tomography angiography during investigation of a sudden headache, and to discuss the clinical relevance of this radiological finding.